PENERAPAN BAHAN AJAR DIGITAL BERBASIS HEYZINE FLIPBOOK TERHADAP HASIL BELAJAR KOGNITIF PADA SISWA SMKN 4 BOJONEGORO - Dita Aulia Sunaryo; Nugrahani Astuti; Febriani Lukitasari; Rendra Lebdoyono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the implementation of learning, students' cognitive learning outcomes, and students' responses after implementing Heyzine Flipbook-based digital teaching materials on poultry-based dishes at SMKN 4 Bojonegoro. This quantitative study employed a One Group Pretest-Posttest Design (pre-experimental) involving 36 students from Class X Culinary 1 and 35 students from Class X Culinary 2. Data were collected through observation, tests, and questionnaires, and analyzed using quantitative/statistical analysis, the N-Gain test, and the Paired Sample t-Test. The results showed that the learning implementation was categorized as very good. The average score increased from 70.00 to 75.00 in Class X Culinary 1 and from 60.00 to 85.00 in Class X Culinary 2. The Paired Sample t-Test showed a significance value (2-tailed) of <0.001, indicating a significant difference between the pre-test and post-test scores. Students' responses ranged good. Therefore, the implementation of Heyzine Flipbook-based digital teaching materials supported the improvement of students' cognitive learning outcomes.